Refrigerator and Oven that are Powered by Solar and Wind Energy (International Journal of Food and Nutritional Sciences, 2021)
Using a thermo electric plate, the project's primary goal is to build a solar and wind-powered refrigerator cum oven. Solar and wind power, which are abundant and cheap, may be used to fuel this endeavour. The cost of this undertaking won't break the freezer. The solar panels and wind turbines in this project are used to recharge a Lead Acid Battery (12V, 1.2 Amp hours), which is then used to power a pelteir thermoelectric device that can provide either a cooling or warming effect, depending on the user's preference. Since this is going in a refrigerator, we need simply the cold setting. The battery is linked to a peltier thermoelectric device, which produces a cooling effect. PIC Microcontroller is being used to show the voltage. The polarity of the peltier plate may be switched by relay and a selection switch. exhaust fan PIC microcontroller solar wind LCD battery Thermo electric plate relay